Autopsy of Communication Messages in Intimate Partner Femicide Cases: Examining Emotional Language and the Mental Health of the Perpetrator - Putra, Fajar Dwi; Unde, Andi Alimuddin; Cangara, Hafied; Sofyan, Andi Muhammad; Saleh, Sadriyani Pertiwi; Irham, Lalu Muhammad; Amukti, Danang Prasetyaning (Scripta Medica, 2025)
Intimate Partner Femicide (IPF) is a tragic phenomenon deeply rooted in cultural, social, and psychological contexts. This study aimed to identify the emotional language patterns and mental health conditions of the perpetrator of the murder case of Ayu Indraswari, who was mutilated into 65 pieces by Heru in 2023. Critical discourse analysis with a linguistic approach was used to examine the communication messages between the perpetrator and victim, which served as the primary data source. The analysis focused on identifying the emotional expressions, manipulations, and language elements that reflected the perpetrator's mental state. The results revealed that the language used by the perpetrator exhibited signs of a psychological disorder characterized by intense emotional manipulation and the use of language that reflected control and dominance over the victim. Expressions of negative emotions such as anger and jealousy were consistently found in perpetrators’ communication, indicating emotional instability and impulsive behavior. The perpetrator's language also showed emotional detachment, extreme selfishness, and premeditation, which are characteristics often associated with antisocial personality disorders. This study provides valuable insights into the relationship between emotional communication patterns and mental states in the context of IPF, highlighting the importance of early detection of risk factors in communication between couples and the development of strategies to prevent violence in intimate relationships.